ECOLOGICAL TOPONYMS AND THEIR TEACHING IN GEOGRAPHY LESSONS - Quzibayeva Ozodakhan Makhmudovna; Muhammedjonova Nigora Zafarjon qizi (EPRA International Journal of Research and Development (IJRD), 2023)
Issues such as the need for a socio-geographical approach to the study of ethnoecological culture, methods of socio-geographical research of the territorial aspects of ethnoecological culture, differentiation of the Fergana Valley area in the "nature-population-population" system, directions of using samples of ethnoecological culture for the purposes of social economic development of the territory are covered.